Integration of Challenge Based on STEM Learning Assisted by 2D Game Interactive Scratch to Numeracy Literacy - Jauhari, Wahid; Alyana Aurellia Putri Arifadewi; Fatya Azizah; Adi Satrio Ardiansyah (Unnes Journal of Mathematics Education, 2024)
This research is development research of 2D games based on Scratch integrated challenge based on STEM context learning in the context of weather station. The aims of developing learning media which is feasible in terms of material and media, and has a positive response from students. The media will facilitate learners in interesting 2D visualization, various interactive activities, and presentation of contextual materials and problems around the elements of STEM context themed weather station. The challenge based on STEM context learning model used will train learners in constructing their knowledge independently so that it can encourage the improvement of learners' numeracy literacy skills. The research method in the form of Research and Development with the ADDIE model has been carried out by considering the material feasibility test, media feasibility test, and learner response assessment. The results of descriptive statistical analysis were conducted after the data were collected using a questionnaire. The results show that the media learning media is said to be feasible in terms of material with a percentage of 91.02% and feasible in terms of media with a percentage of 90.23%. The media fulfils average completeness, proportion completeness, and excellent N-Gain value at 0.77. The media has a positive response of 89.54% from students. Thus, the media is said to be feasible in terms of material and media, effective, and has a positive learner response to improve the numeracy literacy skills of students to boost PISA results so that the ideals of “Indonesia Emas 2045” can be achieved.